Serious and Persistent Mental Illness Treatment and Support Services in Ohio: Perceptions from Consumers, Family Members, and Service Providers - R. Thomas Sherba; Julia Ashwood; Sarah Kriebel; Hannah MacDowell (Ohio Journal of Public Health, 2025)
Background: Given the prevalence of unaddressed mental health conditions in the United States, and the unique challenges that mental health service providers face in their therapeutic work with people living with serious and persistent mental illness (SPMI), it is imperative to understand how and where current services are meeting or falling short according to consumers of SPMI services, their family members, and service providers. Methods: Utilizing a mixed-methods approach, SPMI recovery-oriented practices were assessed throughout Ohio. Data were collected from 332 participants (consumers of SPMI services, their family members, and SPMI service providers) via focus groups and surveys from June through November 2020. Results: Overall, consumers and family members were satisfied with current services but felt negative about the process of finding services. Family members discussed that the behavioral health system did not do a good job of explaining what services were available and how to access those services. While participants generally held a positive perception that the mental health treatment system embraced the core principles of recovery, they overwhelmingly reported that service expansion was needed, both in terms of additional services and a higher volume of existing services, and they discussed the need to combat stigma. Most participants reported that they had perceived negative attitudes toward persons living with SPMI. Two-thirds of service providers perceived negative attitudes in service delivery. Conclusion: Findings illustrate aspects of SPMI treatment and support services as possible areas for improvements, such as heightening community outreach and education, employing navigators, expanding transportation and telehealth options, and expanding crisis services. To address stigma, there were many calls across participant types for increased community education on SPMI and what it means to live with SPMI, with an outreach focus on reframing and positive community messaging.
Keywords: SPMI; Recovery-oriented practices; Stigma; Mental health; Mixed-methods